City in Sight Dutch Dealings with Urban Change - Duyvendak, Jan Willem; Hendriks, Frank; van Niekerk, Mies (NICIS, 2009)
City in Sight presents recent scholarship on the various issues facing today's Dutch metropolitan areas, including immigration and the growing diversity among the urban population, urban restructuring and neighborhood renewal, shifts in urban governance, and the promotion of active citizenship. With its wealth of information and up-to-date research, this text will appeal to scholars of urban politics and social history from all over the globe.